THE TRANSPOSITION OF THE INITIAL CREATION OF WOMEN IN AL-QUR’AN TO AL-KITAB: JULIYA KRISTEVA'S INTERTEXTUALITY ANALYSIS - Aziz Bashor Pratama; Moh. Arif Rakman Hakim (Department Islamic Education, Faculty of Education and Teacher Traning, Universitas Islam Bandung, 2024)
This paper examines the Qur'ānic transposition of Al-Kitab on the understanding that the initial creation of women came from the rib of men. It seems that this discussion arises not from the narrative of the Qur'anic text that explicitly explains it, but only from the narrative of previous interpretations and Hadith narrated by Bukhari and Muslims. This research formulates two problems, first, how the concept of the initial creation of women according to the Qur'an and Al-Kitab, and second, how the transposition of the Qur'an to Al-Kitab. To analyze texts that have a relationship with each other, this paper uses Kristeva's intertextuality approach. This article concludes that the transposition of the Qur'an to the Bible in Kristeva's analysis contains several elements, namely; the connection of substance or excerpt regarding the purpose of the creation of pairs to complement each other and produce offspring, the contradiction between the text of the Qur'an and Al-Kitab which contains elements of haplology occurs in the abrogation of the Qur'anic text which states that women come from the ribs of men, defamiliarization or changes in meaning conveyed by the Qur'an implicitly about the initial creation of women and demystification which occurs when the Qur'anic text changes the definition of the initial creation of women who are the same as men so that this difference creates Qur'anic opposition to the concept of Al-Kitab or conversion.